Thrombocytopenia and Clinical Outcomes in Intracerebral Hemorrhage: A Retrospective Multicenter Cohort Study. Issue 2 (February 2021) - Mrochen, Anne; Sprügel, Maximilian I.; Gerner, Stefan T.; Sembill, Jochen A.; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji B.; Huttner, Hagen B.
Abstract : Background and Purpose: The impact of platelets on hematoma enlargement (HE) of intracerebral hemorrhage (ICH) is not yet sufficiently elucidated. Especially the role of reduced platelet counts on HE and clinical outcomes is still poorly understood. This study investigated the influence of thrombocytopenia on HE, functional outcome, and mortality in patients with ICH with or without prior antiplatelet therapy (APT). Methods: Individual participant data of multicenter cohort studies (multicenter RETRACE program [German-Wide Multicenter Analysis of Oral Anticoagulation-Associated Intracerebral Hemorrhage] and single-center UKER-ICH registry [Universitätsklinikum Erlangen Cohort of Patients With Spontaneous ICH]) were grouped into APT and non-APT ICH patients according to the platelet count, that is, with or without thrombocytopenia (cells <150×10 9 /L). Of all patients, 51.5% (1124 of 2183) were on vitamin K antagonist. Imbalances in baseline characteristics including proportions of vitamin K antagonist patients were addressed using propensity score matching. Outcome analyses included HE (>33%), as well as mortality and functional outcome, after 3 months using the modified Rankin Scale, dichotomized into favorable (modified Rankin Scale score, 0–3) and unfavorable (modified Rankin Scale score, 4–6). Results: Of overall 2252 ICH patients, 11.4% (52 of 458) under APT and 14.0% (242 of 1725) without APT presented with thrombocytopenia on admission. The proportion of patients with HE was not significantly different between patients with or without thrombocytopenia among APT and non-APT ICH patients after propensity score matching (HE: APT patients: 9 of 40 [22.5%] thrombocytopenia versus 27 of 115 [23.5%] nonthrombocytopenia, P =0.89; non-APT patients: 54 of 174 [31.0%] thrombocytopenia versus 106 of 356 [29.8%] nonthrombocytopenia, P =0.77). In both (APT and non-APT) propensity score matching cohorts, there were no significant differences regarding functional outcome. Mortality after 3 months did not differ among non-APT patients, whereas the mortality rate was significantly higher for APT patients with thrombocytopenia versus APT patients with normal platelet count (APT: 29 of 46 [63.0%] thrombocytopenia versus 58 of 140 [41.4%] nonthrombocytopenia, P =0.01; non-APT: 95 of 227 [41.9%] thrombocytopenia versus 178 of 455 [39.1%] nonthrombocytopenia, P =0.49). Conclusions: Our study implies that thrombocytopenia does not affect rates of HE and functional outcome among ICH patients, neither in patients with nor without APT. In light of increased mortality, the significance of platelet transfusions for ICH patients with thrombocytopenia and previous APT should be explored in future studies. Abstract : Supplemental Digital Content is available in the text.